Penerapan Model Pembelajaran Kooperatif Tipe Lottery Card (Kartu Arisan) untuk Meningkatkan Kemampuan Pemahaman Konsep Matematis Siswa Kelas X MAN Salido - Eliza, Rivdya; Putri, Riza Setia Eka (Universitas Islam Negeri Imam Bonjol Padang, 2018)
The Aim of this research were to figure out the learning concept comprehension of students at class X at MAN Salidoin the academic year of 2016/2017 through Cooperative Studying Model Lottery Card Type (Arisan's Card). This was a quasi experimental research with Randomized Control Group OnlyDesign.The population of this research was of students at class X at MAN Salidoin the academic year of 2016/2017. Then, found that students as the experimental class and the control class. To get the class sample test done first then normality, its homogeneity and similarity in average for all classes of the population. After all the class known to normal, homogenous and have the same average then conducted the election of class sample randomly. Before testing the hypotheses, firstly applied the normality test and homogenety test to the sample. Then, tested the hypotheses by applying t-test formula. He got that test t (1,838) > tabel t (1,645) with 0,05 degree of freedom and with 95 % level of credence. Then he concluded that null hypothesis (H0) and the alternative hypothesis (H1) is accepted. So, the ability of the students in understanding Math Concept is higher through the Cooperative Studying Model Lottery Card Type (Arisan's Card) than the students taught through conventional learning.Keywords: Understanding on mathematic concept’s ability, learning model of cooperative (Lottery card).